2006
DOI: 10.3892/ijo.29.3.625
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 inhibitor and interferon-β synergistically induce apoptosis in human hepatoma cells in vitro and in vivo

Abstract: Recent clinical trials have shown that interferon (IFN) is effective for chemoprevention against hepatocellular carcinoma (HCC). However, it remains controversial as to whether IFN exerts direct cytotoxicity against HCC. Cyclooxygenase (COX)-2 also plays a role in hepatocarcinogenesis and may mediate resistance to apoptosis in HCC. Therefore, we aimed to elucidate the combined effect of COX-2 inhibitor, NS-398, and IFN on in vitro growth suppression of HCC using 3 hepatoma cell lines (HepG2, PLC/PRF/5, and Huh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…IFN-b activation of MSCs led to increases in macrophage TNF-a and antagonized its attenuation by IL-1b-activated MSC CM, despite the synergistic interaction of IFN-b with IL-1b to increase PGE2 secretion. Upregulation of NF-jB activity and COX-2 transcription by IFN-b has been reported in Huh7 cells 43 and microglia 44 and IFN-c has previously been reported to increase COX-2 expression and secretion of PGE2 from MSCs. 45,46 However, discrepancies in cell type and source as well as higher concentrations of IFN-c make comparisons with the current study difficult.…”
Section: Discussionmentioning
confidence: 91%
“…IFN-b activation of MSCs led to increases in macrophage TNF-a and antagonized its attenuation by IL-1b-activated MSC CM, despite the synergistic interaction of IFN-b with IL-1b to increase PGE2 secretion. Upregulation of NF-jB activity and COX-2 transcription by IFN-b has been reported in Huh7 cells 43 and microglia 44 and IFN-c has previously been reported to increase COX-2 expression and secretion of PGE2 from MSCs. 45,46 However, discrepancies in cell type and source as well as higher concentrations of IFN-c make comparisons with the current study difficult.…”
Section: Discussionmentioning
confidence: 91%
“…Enhancement of TRAIL-mediated apoptosis by NSAIDs has been occasionally related to decreased levels of survivin (Gaiser et al, 2008;Lu et al, 2008). More frequently, however, upregulation of TRAIL-R1/DR5 has been reported after NSAID treatment, in particular after treatment with celecoxib (Liu et al, 2006;Nakamoto et al, 2006;Yamanaka et al, 2006;He et al, 2008). Also some upregulation of CD95, TNF-R1, and DR4 surface expression has been reported in hepatocellular carcinoma after COX-2 inhibition by celecoxib (Kern et al, 2006), but these death receptors were not involved in colon and prostate cancer cells after sulindac sulfide treatment, where DR5 was selectively upregulated (Huang et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…Lee et al 14) demonstrated an increased antiproliferative effect by the combination of IFN-α· (1,000 IU/mL) and celecoxib (10-50 µM/mL) or curcumin (10-50 µM/mL) in non-small cell lung cancer (NSCLC). Nakamoto et al 17) showed an enhanced antitumor effect by the combined use of IFN-β (5 × 10 4 IU, 3/week) and NSAID, NS-398 (15 mg/kg, every day) in nude mice bearing hepatocellular carcinoma (HCC). In the present study, IFN-β and celecoxib demonstrated an antiproliferative activity on U87 human glioma cells in a dose-dependent manner, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IFN-α/β up-regulates the amount of COX-2 protein and mRNA levels via STAT activation in human hepatoma cells or NSCLC, A549 cells 1,14,17) . The relationship between maximal tolerated doses of IFN-β and the induction of down-regulation of STAT1 signaling has not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%